2017
DOI: 10.1111/cts.12477
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Target Microdosing – A Novel Drug Development Approach: Proof of Concept, Safety, and Feasibility Study in Humans

Abstract: Intra‐Target Microdosing (ITM) is a novel drug development approach aimed at increasing the efficiency of first‐in‐human (FIH) testing of new molecular entities (NMEs). ITM combines intra‐target drug delivery and “microdosing,” the subpharmacological systemic exposure. We hypothesized that when the target tissue is small (about 1/100th of total body mass), ITM can lead to target therapeutic‐level exposure with minimal (microdose) systemic exposure. Each of five healthy male volunteers received insulin microdos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Moreover, data to date suggest that prediction of V and CL for microdose studies is highly reliable . We have previously reported POC studies in rats and humans (described below) . To our knowledge this is the first conceptual description of ITM in drug development.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, data to date suggest that prediction of V and CL for microdose studies is highly reliable . We have previously reported POC studies in rats and humans (described below) . To our knowledge this is the first conceptual description of ITM in drug development.…”
Section: Introductionmentioning
confidence: 94%
“…Since a microdose is defined as 1/100 th of the anticipated pharmacological dose calculated on a total body weight basis, when such a dose is administered into 1/100 th of the body mass or less, pharmacological concentrations are briefly (seconds to minutes) generated in the target tissue before entering the general circulation as a subpharmacological dose (microdose) (Figure ). The duration of such exposure can be increased by the use of a tourniquet or other methods, as we have demonstrated (and see below under POC studies) . Drugs could be administered at constant or varied infusion rates with different durations and concentrations to reflect desired tissue exposure–response time profiles and modeling requirements (see below under “ITM measurement, computational, and modeling considerations”).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITM can then be used to obtain pharmacodynamic, biomarker and MOA data in the target tissues/compartments, and simultaneous systemic microdose data from the rest of the body, for incorporation into models of the microdose to therapeutic dose range. A particularly attractive aspect of ITM is the possibility of comparing symmetrical organs (for example, hands, kidneys and brain hemispheres), whereby one receives the ITM intervention and therefore therapeutic-level exposure while the other is exposed to a systemic microdose, allowing testing across the microdosetherapeutic-level exposures in real time in the same individuals 28,66,70 .…”
Section: Intratarget Microdosingmentioning
confidence: 99%
“…A proof-of-concept human ITM study used insulin administered into the radial artery to demonstrate the feasibility of obtaining pharmacodynamic and MOA data (glucose plasma levels and [ 18 F]fluorodeoxyglucose uptake into muscle tissue) in the ipsilateral hand 70 . The study also demonstrated the utility of control and simultaneous contralateral systemic microdose-level measurements in modelling the microdose versus therapeutic-level dose range.…”
Section: Intratarget Microdosingmentioning
confidence: 99%